THE STRESS MANAGEMENT PRACTICES OF BASIC EDUCATION TEACHERS IN THE IMPLEMENTATION OF MODULAR DISTANCE LEARNING (MDL) IN GASAN DISTRICT: BASIS FOR ENHANCED PROPOSED WELLNESS PROGRAM - Evangelista, Maricel (International Journal of Arts, Sciences and Education, 2023)
Teachers faced difficulties relating to their personal and professional obligations, worries about students' well-being that went beyond academics, and dissatisfaction with the administration during the 2020–2021 academic years as they struggled to educate learners amid the COVID–19 PANDEMIC. Job-related stress may result in teacher shortages, a decline in mental health, and ultimately worse outcomes for pupils if instructors are not given enough support and inclusion. Thus, the main purpose of the study is to identify the causes, effects of stress, and coping mechanisms of basic education teachers in the District of Gasan during Modular Distance Learning. The respondents are Grade 6, 10, and 12 basic education teachers in the District of Gasan. All of the respondents participated in the survey using the purposive sampling method. The research utilized a descriptive research design, using a survey questionnaire as the primary research instrument. In the analysis and interpretation of data percentage, frequency, weighted mean, and rank order will be used.